Análise da transferência dos recursos financeiros municipais para manutenção e desenvolvimento do ensino sobre o enfoque do princípio da eficiência - Santos, Áquila Priscila Souza (2023)
It is known that it is up to the State to guarantee Education, as described in the Major Law. However, is it enough just to provide a school place to guarantee education? The Executive Power, in essence, is responsible for proposing the way in which financial resources are transferred to school funds. The way it is done is based on federal law and establishes a series of requirements and documents that must be completed, so that the municipal school fund is approved for the consequent partnership. That is, there is a whole process for obtaining financial resources. The work discusses the local state action promoting, in accordance with the laws that govern the theme, the conditions for Education, a fundamental social right, to be guaranteed, in its essence, to students. Specifically, the analysis of the way in which the entire process for the transfer of municipal financial resources for the maintenance and development of education to the municipal school funds of Uberlândia-MG is carried out, relating to the applicability of the principle of efficiency, a constitutional principle that governs Public Administration . The nature of the research and development took place, objectively, from the qualitative - descriptive approach, since there is no possibility of quantifying the ideal time for the process to receive municipal financial resources to be carried out so that effective application of the principle under discussion. Thus, it is a basic research, since it does not aim to present an innovative way for school funds to receive financial resources more quickly, but to present the current local reality. Delimiting the instruments and sources chosen for data collection to legislation, doctrines related to the proposed theme and specific case study: step-by-step notes for a municipal school fund to be able to receive municipal financial resources. Developed from the analysis of studies by several researchers who address issues addressed in the work, among which, it is worth mentioning Cunha (2017), Ferraz (2023) and Secchi (2013).